Expression of a hypomorphic Pomc allele alters leptin dynamics during late pregnancy. Issue 1 (April 2020) - Yu, Hui; Thompson, Zoe; Kiran, Sylee; Jones, Graham L; Mundada, Lakshmi; Surbhi,; Rubinstein, Marcelo; Low, Malcolm J
Abstract : Proopiomelanocortin (POMC) neurons in the hypothalamic arcuate nucleus (ARC) are essential for normal energy homeostasis. Maximal ARC Pomc transcription is dependent on neuronal Pomc enhancer 1 (nPE1), located 12 kb upstream from the promoter. Selective deletion of nPE1 in mice decreases ARC Pomc expression by 70%, sufficient to induce mild obesity. Because nPE1 is located exclusively in the genomes of placental mammals, we questioned whether its hypomorphic mutation would also alter placental Pomc expression and the metabolic adaptations associated with pregnancy and lactation. We assessed placental development, pup growth, circulating leptin and expression of Pomc, Agrp and alternatively spliced leptin receptor ( LepR ) isoforms in the ARC and placenta of Pomc ∆1/∆1 and Pomc +/+ dams. Despite indistinguishable body weights, lean mass, food intake, placental histology and Pomc expression and overall pregnancy outcomes between the genotypes, Pomc ∆1/∆1 females had increased pre-pregnancy fat mass that paradoxically decreased to control levels by parturition. However, Pomc ∆1/∆1 dams had exaggerated increases in circulating leptin, up to twice of that of the typically elevated levels in Pomc +/+ mice at the end of pregnancy, despite their equivalent fat mass. Pomc ∆1/∆1 dams also had increased placental expression of soluble leptin receptor ( LepRe ), although the protein levels of LEPRE in circulation were the same as Pomc +/+ controls. Together, these data suggest that the hypomorphic Pomc ∆1/∆1 allele is responsible for the perinatal super hyperleptinemia of Pomc ∆1/∆1 dams, possibly due to upregulated leptin secretion from individual adipocytes.